Transfer of training among teachers attending short courses - Ibrahim, Abu Hassan (1997)
The transfer of training (the application of training in the workplace) is a critical issue faced by all organizations. This issue is concerned with the impact of training on employees and the organization. Trainee's characteristics, training design and organizational support are identified in many studies as the three major factors affecting the transfer of training. This study is aimed at investigating the transfer of training on the Art of Learning courses organized by the Education Department of Pahang. The objectives of the study were: (1) to identify the outcomes of the Art of Learning course; (2) determine the level of learning and transfer of training among course participants; (3) to determine the relationship between the transfer of training and trainee's characteristic, training design and organizational support. Ninety-four teachers out of 120 participants who attended three separate training programs were interviewed. They were asked to rate ten questions regarding trainee's characteristics, twenty questions each regarding training transfer, training design and organizational support. Data were gathered through personal interviews using questionnaires specifically designed for these studies. Three relationships were tested by using Pearson Product - Moment Correlation. Frequenc:ies, mean, median, percentages and t-test were also used in the analysis. The findings from the study showed that there were changes in the level of knowledge, level of skills and level of ability to solve problems among participants after attending training program. However the levels of training transfer among the participants were low . The study also found that the score on trainee's characteristic and training design were high. The score on organizational support was less than the median. The findings indicated a positive and significant correlation between: (1) transter of training and trainee' characteristics, (2) transfer of training and training design. However the finding did not show any relationship between transfer of training and organizational support.